2021
DOI: 10.3389/fchem.2021.774555
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Synthesis of Marine-Derived Ilamycin F Derivatives and Their Antitubercular Activities

Abstract: Tuberculosis (TB) is still a global disease threatening people’s lives. With the emergence of multi-drug-resistant Mycobacterium tuberculosis the prevention and control of tuberculosis faces new challenges, and the burden of tuberculosis treatment is increasing among the world. Ilamycins are novel cyclopeptides with potent anti-TB activities, which have a unique target protein against M. tuberculosis and drug-resistant strains. Herein, ilamycin F, a major secondary metabolite isolated from the marine-derived m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Review highlights included those describing advances in phenazine chemistry over the past decade, 81 a catalogue of 1062 terpenoid NPs produced by bacteria, entitled "Bacterial terpenome", 82 overviews of the biology and chemistry of macrolactins 83 and thiopeptides, 84 how the recording and mining of MS data is transforming NP research, 85 N-N bond formation reactions involved in NP biosynthesis, 86 developing techniques that can be applied to single cells for accelerating microbial NP research, 87 recent highlights of biosynthetic studies on marine bacteria products, 88 a summary detailing 127 halogenated compounds identied from marine actinomycetes (1992-2022), 89 use of synthetic biology to elucidate NP BGCs encoded in Streptomyces genomes, 90 chemical labelling strategies for NP detection and isolation, 91 cryptic halogenation reactions associated with NP biosynthesis, 92 volatile nitrogenous compounds from bacteria, 93 the versatile role of condensation domains in NP biosynthesis, 94 importance of microbial NP databases and their impact in the multi-omics era, 95 diversity, mechanism and selectivity of polyketide b-branching, 96 and an overview of natural antiplasmodial lead compounds (648 NPs from various natural sources; 2013-2019). 97 Other marine bacterial research that made noteworthy contributions to the eld included the enhanced production (3.8-fold increase) of the cytotoxic and antibacterial compound ohmyungsamycin A that was achieved via adenylation domain engineering and optimisation of culture conditions, 98 the semisynthesis of 18 ilamycin F derivatives, several of which had improved anti-tubercular activity compared to the MNP, 99 research on the biosynthesis of anthraquinone-fused enediynes (e.g. dynemicin A) that has delivered insights into the biosynthetic enzymes and pathways associated with this rare chemotype, 100 and identication of a C-glycosyltransferase involved in the biosynthesis of the pyranonaphthoquinone medermycin.…”
Section: Natural Product Reports Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Review highlights included those describing advances in phenazine chemistry over the past decade, 81 a catalogue of 1062 terpenoid NPs produced by bacteria, entitled "Bacterial terpenome", 82 overviews of the biology and chemistry of macrolactins 83 and thiopeptides, 84 how the recording and mining of MS data is transforming NP research, 85 N-N bond formation reactions involved in NP biosynthesis, 86 developing techniques that can be applied to single cells for accelerating microbial NP research, 87 recent highlights of biosynthetic studies on marine bacteria products, 88 a summary detailing 127 halogenated compounds identied from marine actinomycetes (1992-2022), 89 use of synthetic biology to elucidate NP BGCs encoded in Streptomyces genomes, 90 chemical labelling strategies for NP detection and isolation, 91 cryptic halogenation reactions associated with NP biosynthesis, 92 volatile nitrogenous compounds from bacteria, 93 the versatile role of condensation domains in NP biosynthesis, 94 importance of microbial NP databases and their impact in the multi-omics era, 95 diversity, mechanism and selectivity of polyketide b-branching, 96 and an overview of natural antiplasmodial lead compounds (648 NPs from various natural sources; 2013-2019). 97 Other marine bacterial research that made noteworthy contributions to the eld included the enhanced production (3.8-fold increase) of the cytotoxic and antibacterial compound ohmyungsamycin A that was achieved via adenylation domain engineering and optimisation of culture conditions, 98 the semisynthesis of 18 ilamycin F derivatives, several of which had improved anti-tubercular activity compared to the MNP, 99 research on the biosynthesis of anthraquinone-fused enediynes (e.g. dynemicin A) that has delivered insights into the biosynthetic enzymes and pathways associated with this rare chemotype, 100 and identication of a C-glycosyltransferase involved in the biosynthesis of the pyranonaphthoquinone medermycin.…”
Section: Natural Product Reports Reviewmentioning
confidence: 99%
“…Other marine bacterial research that made noteworthy contributions to the field included the enhanced production (3.8-fold increase) of the cytotoxic and antibacterial compound ohmyungsamycin A that was achieved via adenylation domain engineering and optimisation of culture conditions, 98 the semi-synthesis of 18 ilamycin F derivatives, several of which had improved anti-tubercular activity compared to the MNP, 99 research on the biosynthesis of anthraquinone-fused enediynes ( e.g. dynemicin A) that has delivered insights into the biosynthetic enzymes and pathways associated with this rare chemotype, 100 and identification of a C -glycosyltransferase involved in the biosynthesis of the pyranonaphthoquinone medermycin.…”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%
“…Very recently, a wide range of new ilamycins/rufomycins were described, differing mainly in their combination of different amino acid oxidation levels and the N -prenyl substituent of the tryptophan subunit (alkene, epoxide, diol) [ 22 ]. In addition, a total of 18 new Ilamycin F (Ila F) derivatives were obtained by semi-synthesis from Ila F through modification of the nitrotyrosine as well as δ-hydroxyleucine unit [ 23 ]. Ilamycin E (Ila E) has been found to be one of the most active examples so far (MIC: ~10 nM) ( Figure 1 ), being more active than the rifampicin used as a positive control [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a total of 18 new Ilamycin F (Ila F) derivatives were obtained by semi-synthesis from Ila F through modification of the nitrotyrosine as well as δ-hydroxyleucine unit [ 23 ]. Ilamycin E (Ila E) has been found to be one of the most active examples so far (MIC: ~10 nM) ( Figure 1 ), being more active than the rifampicin used as a positive control [ 22 , 23 , 24 , 25 ]. Structure–activity relationship (SAR) studies of the isolated derivatives indicated that cyclized compounds such as Ila E are more active than open-chain leucine derivatives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation